Car Crash Speed Estimates Not Biased by Leading Questions. (September 2021) - Raghunath, N.; Fultz, A.A.; Sanchez, C.A.
Individuals' recollections of events have been shown to be susceptible to external factors, especially when it comes to speed estimations. This study explored the impact of perceptually disfluent presentations and presentation modalities of car crashes on observers' estimations of speed, in addition to the testing the currently accepted effect of leading questions on the same. Participants viewed videos or images of car crashes, presented in higher or lower visual quality, and reported how fast the vehicles were traveling when they "made contact" or "smashed into" each other. Results showed that neither question phrasing, visual quality, nor presentation modality of car crashes affected speed estimates. Individuals who believe cars to travel at higher speeds, however, in general estimated higher speeds when viewing car crash images, especially when presented in lower visual quality. These findings suggest that a combination of external factors may influence event recall depending on individual's pre-existing beliefs about car speeds, and should be considered prior to obtaining eyewitness accounts.